2018
DOI: 10.1590/s1413-41522018134577
|View full text |Cite
|
Sign up to set email alerts
|

Potencial de índices urbanísticos como indicadores da qualidade térmica do ambiente urbano

Abstract: RESUMO A qualidade térmica do ambiente urbano é um dos problemas enfrentados pelas cidades atualmente. A forma de ocupação urbana altera o balanço de energia nas cidades, provocando frequentemente um aquecimento do ar nas camadas intraurbanas e criando microclimas variados. No entanto, mapear os microclimas urbanos possibilitando apoio à tomada de decisões de planejamento urbano é uma tarefa complexa e de longo prazo. Procurando demonstrar as potencialidades térmicas oferecidas por alguns índices urbanísticos … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Studies have been conducted to investigate the effects of the occupancy factor, floor area index, and vegetation cover index on urban microclimate temperature. They have also concluded that the range of values for the vegetation factor can lead to more significant temperature differences [60]. One study has been conducted using the unsteady Reynolds-averaged Navier-Stokes (URANS) equations for computational fluid dynamics (CFD) simulations to analyze the cooling effect of street trees during heatwaves in urban environments.…”
Section: Urban Development Elements and The Urban Heat Environmentmentioning
confidence: 99%
“…Studies have been conducted to investigate the effects of the occupancy factor, floor area index, and vegetation cover index on urban microclimate temperature. They have also concluded that the range of values for the vegetation factor can lead to more significant temperature differences [60]. One study has been conducted using the unsteady Reynolds-averaged Navier-Stokes (URANS) equations for computational fluid dynamics (CFD) simulations to analyze the cooling effect of street trees during heatwaves in urban environments.…”
Section: Urban Development Elements and The Urban Heat Environmentmentioning
confidence: 99%